Estrategias metodológicas activas para el logro de aprendizajes significativos. Año lectivo 2023 – 2024 - Japón Vanegas, Arianna Elizabeth (2024)
The application of active methodological strategies in the development of the Biology teaching-learning process is important because through participatory and motivating processes, it promotes in students the construction of meaningful learning, which substantially improves their academic performance. This research had as objective: << To enhance the academic performance of students, through the construction of meaningful learning through the application of active methodological strategies, in the development of the teaching-learning process of Biology of the third year of Technical Baccalaureate in Accounting, of "Daniel Álvarez Burneo" Educative Unit, academic year 2023 - 2024>>. The inductive method was used for its development, since it began with the direct observation of the development of the classroom process, evidencing a problem, which led to the search in bibliographic resources to find alternative solutions. With respect to the qualitative approach, characteristics of the teaching-learning process were identified, such as: the lack of application of active methodological strategies in the development of such process, which generates demotivation and lack of interest in the students. According to the nature of the information, it is Participatory Action Research (PAR), with the diagnosis of the problem, there was direct intervention, through the development of the intervention proposal, with the group of students, achieving an improvement in the identified situation; it is also transversal; since it considers a relatively short period of time. The results obtained through the evaluation and research instruments showed that the active methodological strategies implemented contributed to improve the students' learning results, since their motivation and interest in learning was awakened. It is concluded that the academic performance of students is enhanced by the application of active methodological strategies in the development of the teaching-learning process of Biology. Key words: Teaching-learning, academic performance, active participation, motivation.